The time of our lives in Bristol: Developing positive flexibility for employees and services (London, 1999)
Outlines the processes and outcomes of the first year of a project in Bristol City Council set up as a national social partner pilot by the TUC and the Employers’ Organisation for Local Government. It documents practical action taken in Bristol and partnership working between unions and management to jointly identify services which could be delivered more effectively, including changes in working patterns to assist employees meet personal and family commitments